Feasibility of Sexual Health and Contraceptive Web Services for Adolescents and Young Adults: Retrospective Study of a Pilot Program on Reunion Island - Danielle Reynaud; Nicolas Bouscaren; Emmanuelle Cartron; Catherine Marimoutou (JMIR Publications, 2024)
Abstract BackgroundSexual health indicators for adolescents and young adults (AYAs) aged between 13 and 25 years are particularly poor on Reunion Island. Access to accurate information as well as sexual health and contraceptive services are vital to maintaining sexual well-being. Teleconsultations offer a promising approach to addressing the sexual health and contraceptive needs of AYAs who are more susceptible to engaging in unprotected sexual intercourse. However, the literature on digital sexual health services for this demographic group is limited. ObjectiveThis study aims to describe the feasibility of a pilot sexual health and contraceptive teleconsultation web service used by AYAs on Reunion Island. MethodsA descriptive, retrospective study was conducted at the Reunion Island University Hospital Center using a convenient sample. Eligible participants were informed about the program through various communication channels, including seminars for health care professionals, radio broadcasts, posters, flyers, press articles, videos, and social media posts. AYAs accessed a web-based platform named SEXTUOZE from December 15, 2021, to September 30, 2022, that offered sexual health information and teleconsultations. Data collected included participant and teleconsultation characteristics, patient satisfaction, and the quality of completeness of medical records. ResultsA total of 22 teleconsultations were scheduled and 7 were completed, all via synchronous video communication (duration: median 35 min). Overall, 4731 sessions were generated on the SEXTUOZE website. Reasons cited for accessing the web services were to seek sexual health advice (8/22, 36%), receive an initial birth control prescription (12/22, 55%), and inquire about condom prescriptions (2/22, 9%). ConclusionsWhile teleconsultation use for sexual health was initially low, it rose toward the end of the study period. Considering all elements of the implementation theory, future research should design interventions that not only are more operative and tailored but also ensure their adoption and sustainability in various health contexts.